Skin--The Next User Interface. - Steimle, Jurgen (Computer (00189162), 2016)
Although there are numerous technical and ethical challenges, making sensors and output components compatible with elastic skin has the potential to offer an unprecedented level of directness and expressiveness in mobile computing.